THE SOCIETAL CONTEXT OF SIGNIFICANT OTHERS: COMPARATIVE PERCEPTIONS OF MOTHER- AND FATHERHOOD IN SWEDEN, FINLAND AND ESTONIA - Helbe Podder; Kaire Poder (European Scientific Journal, ESJ, 2015)
The article focuses on the attitudes of the parents of three different countries—Sweden, Finland, and Estonia—towards the balance between work and family life in a particular environment of the welfare state through their evaluation of the social context. The aim of this analysis is to determine the extent to which family policies have successfully met the expectations of parents. We have found differences in the expectations of parents towards supportive measures offered by the state that would help combine work and family life in the countries studied, and in the respondents’ evaluations of the social environment they live in. On the basis of this analysis it is possible to argue that the participating Swedish and Finnish parents are highly satisfied with their position in the context of their respective countries, while Estonian parents feel insecure.